2016
DOI: 10.1080/09638288.2016.1194899
|View full text |Cite
|
Sign up to set email alerts
|

Which outcomes are most important to people with aphasia and their families? an international nominal group technique study framed within the ICF

Abstract: This is the accepted version of the paper.This version of the publication may differ from the final published version. Permanent repository link:http://openaccess.city.ac.uk/15003/ Link to published version: http://dx.doi.org/10. 1080/09638288.2016.1194899 Copyright and reuse: City Research Online aims to make research outputs of City, University of London available to a wider audience. Copyright and Moral Rights remain with the author(s) and/or copyright holders. URLs from City Research Online may be freel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
105
0
12

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 193 publications
(119 citation statements)
references
References 61 publications
2
105
0
12
Order By: Relevance
“…Hamilton (2000), on the other hand, argues that people with post-stroke aphasia should be encouraged to maintain their pre-stroke identity. This is confirmed by the findings of Wallace et al (2016) who found recovery to normality, including "to be seen as the same person as I was before" (p. 1371) to be an important therapy outcome for people with aphasia. To maintain the pre-stroke identity, attempting to pass then becomes a desirable strategy.…”
Section: Stigma Symbols As Sign Makingsupporting
confidence: 74%
“…Hamilton (2000), on the other hand, argues that people with post-stroke aphasia should be encouraged to maintain their pre-stroke identity. This is confirmed by the findings of Wallace et al (2016) who found recovery to normality, including "to be seen as the same person as I was before" (p. 1371) to be an important therapy outcome for people with aphasia. To maintain the pre-stroke identity, attempting to pass then becomes a desirable strategy.…”
Section: Stigma Symbols As Sign Makingsupporting
confidence: 74%
“…Indeed, the ability to participate in conversation is a treatment outcome prioritised internationally by both people with aphasia and their family members (Wallace et al, 2016a). To achieve this, conversation must be targeted directly (Royal College of Speech and Language Therapists, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…In fact, narrating experiences and events enables PWA to participate in family and social activities, and to (re)develop their identity after the disruptive life event of stroke [18]. Within the World Health Organization’s International Classification of Functioning [19], the ultimate goal of aphasia rehabilitation is to enable PWA to daily participate actively in their natural family environment and community with respect to autonomy, life roles and leisure activities, for example [20]. Activity and participation fosters a healthier quality of life as reflected by research on biographic-narrative intervention [17] and on treatment outcomes important to PWA and their families [20].…”
Section: Introductionmentioning
confidence: 99%